2000
DOI: 10.1007/pl00007269
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent impairment of coronary collateral development in humans

Abstract: The purpose of this study was to evaluate whether age influences collateral development in patients with coronary artery disease. The extent of collateral development to the area perfused by the infarct-related artery was graded, depending on the degree of opacification of the occluded infarct-related artery. We evaluated the extent of collateral development using coronary cineangiography in 102 patients with an acutely occluded infarct-related coronary artery within 12 h after the onset of the first acute myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 27 publications
3
28
2
Order By: Relevance
“…The mean age in the present study was a 59.94 ± 10.13 year which was comparable to that of only diabetic cases in a study from Turkey (in diabetic patients-59.09 ± 8.49 years, in non diabetic patients-58.89 ± 11 years) while CAD was observed at a higher average age in Swiss (64 years) and Japanese studies (62 ± 11 years) [10] [11] [12]. Therefore, it is evident that Indians are being affected at an earlier age.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The mean age in the present study was a 59.94 ± 10.13 year which was comparable to that of only diabetic cases in a study from Turkey (in diabetic patients-59.09 ± 8.49 years, in non diabetic patients-58.89 ± 11 years) while CAD was observed at a higher average age in Swiss (64 years) and Japanese studies (62 ± 11 years) [10] [11] [12]. Therefore, it is evident that Indians are being affected at an earlier age.…”
Section: Discussionsupporting
confidence: 78%
“…In cases with age > 50 years, collaterals were significantly more prevalent compared to less than 50 years (Table 2). Nakae et al [12] also observed higher prevalence of collaterals among cases with age ranging from 55 -63 years, but well developed collaterals were documented less in older patients in their study group while Pohl et al [17] did not find any significant correlation between age and collateral development (measured by coronary flow index). Increasing prevalence of coronary collaterals with age in collateral circulation is more common with RCA than with LAD or circumflex occlusion [19].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, van der Hoeven et al [22] in their study divided patients into two groups (≤ 64 years and ≥ 65 years) and also found no association between higher age and the development of poor collaterals. Conversely, it differed from the reports of Nakae et al [14] and Sun et al [19] who stated that well-developed collaterals were significantly lower in patients older than > 65 years of age. The disparity in the results may be explained by the difference in the methods of coronary collateral assessment and grading of these channels.…”
Section: Discussioncontrasting
confidence: 84%
“…However, there was no statistically significant difference in the prevalence of excellent collaterals between males and females; therefore, there was no association between the patients' sex and the development of excellent collaterals. Although, the present finding differed from the report of Sun et al [19] who stated that well-developed collaterals was significantly lower in female patients, it confirmed the reports of Fujita et al [4] and Nakae et al [14] who also found no significant difference.…”
Section: Discussionsupporting
confidence: 63%
“…Significant coronary narrowing was defined as stenosis of at least 50% of the vessel diameter in any of the main coronary arteries (the left main coronary artery, the left anterior descending coronary artery with its major diagonal branches, the right coronary artery or the circumflex coronary artery with its major marginal one). Collateral vessels were graded according to Rentrop's classification, 15,16 in which 0 = no opacification; 1 = filling of side branches of the artery perfused by way of collateral vessels without visualization of the epicardial segment; 2 = partial filling of the epicardial segment by way of collateral vessels; 3 = complete filling of the epicardial segment by way of collateral vessels. Grading of the collateral vessels was independently performed by 2 angiographers.…”
Section: Cardiac Catheterization and Angiographymentioning
confidence: 99%